Effects of export sophistication on marine pollution: Evidence from Chinese coastal regions - Xina Ji; Xingong Ding; Shuping Lin; Xiaoxuan Xie (PLoS ONE, 2026)
Trade liberalization has accelerated export growth in China’s coastal regions, becoming a major driving force behind local economic development. However, this rapid expansion has also imposed severe environmental pressures on marine ecosystems. As a key indicator for assessing the technological content and quality level of export structures, export sophistication warrants in-depth investigation regarding its potential impact on the marine environment. Drawing on panel data from 11 coastal regions in China between 2011 and 2022, this study employs a two-way fixed-effects model to empirically examine the relationship between export sophistication and marine pollution. The baseline regression results show that higher export sophistication significantly reduces marine pollution. The System GMM dynamic panel analysis further confirms a lagged, long-term pollution-reducing effect. Moreover, environmental regulation, port size, and industrial structure weaken this effect, indicating that the environmental benefits of export sophistication diminish under stricter regulatory conditions, larger port scales, or more advanced industrial structures. The mediation analysis reveals that green technological innovation partially transmits the impact of export sophistication on pollution reduction. Robustness checks, including the exclusion of provinces with extreme pollution levels, confirm the stability of the findings. Heterogeneity analysis further shows that the effects vary across different types of marine pollutants. This study enriches the research perspective on the link between export sophistication and environmental pollution, providing theoretical foundations and policy implications for promoting coordinated development between export structure optimization and marine environmental governance.